The Role Of SMM For Creating The Destination Image Of Uzbekistan - Khaydarova Dilora Ikhtiyorovna (Cita Konsultindo Research Center, 2022)
It is no secret that in today’s globalized world, social networks play an important role in every aspect of life, and tourism is no exception. Social networks are used to attract tourists or to form the image of the destination in the minds of potential consumers. The aim of study: scrutinizing ways to development the image of destination in Uzbekistan through social media marketing and creating proposals and recommendations for its implementation. The article uses the method of analysis of the creating the image of destination through using SMM and also author uses foreign practice to compare and acquire proposals for improving destination image of Uzbekistan. Also graphs were used to represent the statistic dynamics. With a broad literature review conducted, it was noted that in the social media marketing mainly used as information sources in their decision-making process. The purpose of this study was to determine what role social media as an information source has in the decision making of tourists when choosing the destination and how we can form the image of the destination in the minds of potential tourists. The results of this study indicated that tourists use social media as an information source to some extent when making a decision about destination. Social media was found to be a credible source of information and has a slight influence on their decision-making process to tourists.